SOCIODEMOGRAPHIC FACTORS ASSOCIATED WITH PARENTING STRESS DURING COVID-19 PANDEMIC - Abidin, Fitri Ariyanti; Fadilah, Syipa Husni; Anindhita, Vidya; Lubis, Fitriani Yustikasari; Qodariah, Laila; Kendhawati, Lenny; Agustiani, Hendriati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
The Covid-19 pandemic is a phenomenon that mental health scholars have not fully understood, which might adversely affect parenting. Previous studies have found that sociodemographic factors influence parenting stress in non-pandemic conditions. However, no study has discussed parenting stress during the Covid-19 pandemic. Therefore, the present study investigates the sociodemographic factors influencing parenting stress during the Covid-19 pandemic. Using a cross-sectional approach, we applied convenience sampling using online platforms to recruit the participants. Seven hundred ninety parents aged 20-57 participated in this study (mothers = 740, fathers = 50). The validated Indonesian version of the Parenting Stress Scale was administered online to measure parenting stress. The results identified that mothers experienced parenting stress more than fathers (t(788) = -2.83; p = 0.005; d = -3.28; 95% CI [-5.55; -1.00]). Furthermore, it revealed that financial condition was the only predictor of the parenting stress experienced by fathers (β = 0.39, p = 0.02). Apart from the financial condition, working status (β = -0.08, p = 0.04), educational background (β =-0.10, p = 0.02), and marital status (β = 0.13, p = 0.00) also predicted the level of parenting stress in mothers. Several sociodemographic variables associated with maternal parenting stress indicate the necessity of interventions to promote mothers' mental health, who are more prone to parenting stress than fathers.